MOOD DISTURBANCES IN PARENTS OF CHILDREN HAVING POOR ACADEMIC PERFORMANCE - Dr Divya KG, Dr Neeraj Raj B, Pooja V, Dr Gopal Das CM, Dr.V.Anupama (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: A child with poor academic performance induces complex feelings in the parentswho experience stress in coping with the child’s disability. But parent’s well-being is essentialfor managing the child’s condition. In this background the present study is planned to assess themood disturbances in parents of children having poor academic performance attending Psychiatry OPD.